Employment Status and Workforce in the Formal and Informal Sector: A Case Study of district Lahore - Durdana Qaiser Gillani; Muhammad Zahid Naeem (Journal of Political Studies, 2017)
The present study highlights the employment status and work force in the formal and informal sector in the urban labor market. The effects of socio- economic and human capital variables are analyzed on the formal and informal sector employment. A household survey is conducted in urban areas of district Lahore. Data is collected from 321 participants of the urban labor market. The multinomial log it results indicate that education, age, gender, father’s education and presence of assets are the most important factors which determine the employment status of workers in urban areas of district Lahore. The results suggest more employment opportunities to absorb the rapidly growing population in urban areas of district Lahore.